Equilibrium Mispricing in a Capital Market with Portfolio Constraints - Basak, Suleyman; Croitoru, Benjamin (Review of Financial Studies, 2000)
This article develops a general equilibrium, continuous time model where portfolio constraints generate mispricing between redundant securities. Constrained consumption-portfolio optimization techniques are adapted to incorporate redundant, possibly mispriced securities. Under logarithmic preferences, we provide explicit conditions for mispricing and closed-form expressions for all economic quantities. Existence of an equilibrium where mispricing occurs with positive probability is verified in a specific case. In a more general setting, we demonstrate the necessity of mispricing for equilibrium when agents are heterogeneous enough. The construction of a representative agent with stochastic weights allows us to characterize prices and allocations, given mispricing occurs.